(3OQGSGJ LOhi GdeTQhY (B/s - (3GdUMf, eMeO aQjOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2005)
(3GdGWGQ GdYGe dOQGSGJ GdLOhi, GdJYQa Ydi GdaQU GdGSJKeGQjI hGYOGO OQGSGJ GdLOhi GdJegjOjI, GdOQGSGJ GdJShjbjI, GdOQGSGJ GdafjI, GdOQGSI GdeGdjI, OQGSGJ GdLOhi GdJfXjejI ddCaQGO, OQGSGJ GdQHMjI GdGLJeGYjI(B.s
(3GdeQGLY U(B.293s
Keywords: (3EOGQI GdeTGQjYs; (3GdGSJKeGQs; (3Jbjje GdCOGAs; (3VHW GdLhOIs